INOVASI DEODORAN ALAMI BERBASIS DAUN BELUNTAS UNTUK KESEHATAN DAN EKONOMI KELUARGA - Faikah Dyah Utami; Mariyani Mariyani; Sririzqi Mutmainnah; Fikri Al-Ghifary (Jurnal Abdi Insani, 2025)
Beluntas leaves (Pluchea indica) contain flavonoids, tannins, and essential oils with antibacterial activity, making them a promising candidate for the development of natural deodorant products that are both safe and environmentally friendly. This community service program was carried out to improve local residents’ knowledge and skills in processing beluntas leaves into value-added products, while also reducing reliance on synthetic chemical deodorants that may pose health risks. The activities involved education and group discussions on the benefits of beluntas, hands-on training covering drying, grinding, extraction, formulation, and packaging techniques, as well as guidance on product marketing. The outcomes showed an increase in community understanding of the role of medicinal plants, improved technical skills in natural deodorant production, and the emergence of small-scale entrepreneurial initiatives based on herbal products. In conclusion, the program successfully achieved its objectives by empowering the community through innovation in beluntas utilization, resulting in positive impacts on both public health and household economic opportunities.